Mapping protein direct interactome of oxidoreductases with small molecular chemical cross-linkers in live cells - Ting Wu; Shang-Tong Li; Yu Ran; Yinuo Lin; Lu Liu; Xiajun Zhang; Lianqi Zhou; Long Zhang; Donghai Wu; Bing Yang; Shibing Tang (Redox Biology, 2023)
Identifying direct substrates of enzymes has been a long-term challenge. Here, we present a strategy using live cell chemical cross-linking and mass spectrometry to identify the putative substrates of enzymes for further biochemical validation. Compared with other methods, our strategy is based on the identification of cross-linked peptides supported by high-quality MS/MS spectra, which eliminates false-positive discoveries of indirect binders. Additionally, cross-linking sites allow the analysis of interaction interfaces, providing further information for substrate validation. We demonstrated this strategy by identifying direct substrates of thioredoxin in both E. coli and HEK293T cells using two bis-vinyl sulfone chemical cross-linkers BVSB and PDES. We confirmed that BVSB and PDES have high specificity in cross-linking the active site of thioredoxin with its substrates both in vitro and in live cells. Applying live cell cross-linking, we identified 212 putative substrates of thioredoxin in E. coli and 299 putative S-nitrosylation (SNO) substrates of thioredoxin in HEK293T cells. In addition to thioredoxin, we have shown that this strategy can be applied to other proteins in the thioredoxin superfamily. Based on these results, we believe future development of cross-linking techniques will further advance cross-linking mass spectrometry in identifying substrates of other classes of enzymes.